Effects of some external treated plant growth regulators on stomatal aperture of cucumber (Cucumis sativus L.) - (:unkn) unknown (ACADEMIC JOURNALS, 2009)
In this study, cucumber (Cucumis sativus L.) seedlings grown singly in standard pots contain compost were exposed to two different concentrations (10(-4) and 10(-6) M) of BA (6-benzyladenine), NAA (alpha-naphthaleneacetic acid) and GA(3) (Gibberellic acid). Plant growth regulators were used as spraying (2 ml) on the lower surfaces of leaves for seven days. Beith alpha and Cengelkoy, which are two elite and widely planting cucumber varieties in Turkey were used and the results were comparatively studied. Stomatal diameters from the epidermal sections of abaxial leaves in 1, 3, 5 and 7th days were examined by image processing and analysis software program. The data proved that, stomatal aperture were affected significantly with BA, NAA and GA3 treatments, but responded variously in all treated plants compared to measurements of the control groups.
Keywords: Cucumber; stomata; benzyl adenine; naphthalene acetic acid; gibberellic acid; VICIA-FABA; ABSCISIC-ACID; EPIDERMAL STRIPS; GAS-EXCHANGE; IN-VITRO; CYTOKININS; RESPONSES; LEAVES; ABA; INHIBITION